Plural Ecologies of Tigers in Indonesian Literature: A comparison of Mochtar Lubis' Harimau! Harimau! and Eka Kurniawan's Lelaki harimau. Issue 148 (2nd September 2022) - Duile, Timo
ABSTRACT: This article explores the changing ecologies in Indonesian literature by drawing on the examples of tigers in two influential novels, namely Mochtar Lubis' Harimau! Harimau! (1975) and Eka Kurniawan's Lelaki harimau (2004). Using the concept of 'plural ecologies' from anthropological research in Southeast Asia, an ecology is understood as a set of relations between humans and non-humans, and it is argued that Mochtar Lubis' novel depicts a setting of conflicting ecologies in which an Islamic-humanist naturalism eventually emerges as the true ecology. The novel stands in the tradition of disenchantment in the wake of modernisation and nation building. But contrary to the assumption that society – and literature – develops towards disenchantment ( penduniaan ), the more recent novel, Lelaki harimau, provides an example of a plural ecology in which the possibility of other relations between humans and non-humans is maintained, as in the novel the tiger emerges as a spirit which dwells in the body of the protagonist. The plural ecologies make different readings of the novel possible and demonstrate that animism is still a relevant factor for the understanding of social reality.